The Influence of Consumer Trust in Offline Stores and Perceived Confidence in Online Stores on Information Search Intention and Purchase Intention of Alfamart Consumers - Abiya Fahira (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
The rapid evolution of retail business models in Indonesia has driven retailers to integrate offline and online shopping channels in order to adapt to shifting consumer behaviors. Alfamart has responded to this transformation by combining its extensive physical store network with the Alfagift digital platform, thereby enhancing consumer access, convenience, and the availability of product information. This study aims to examine the influence of consumer trust in offline stores and perceived confidence in online stores on consumers’ information-seeking intention and purchase intention. A quantitative approach was applied by distributing structured questionnaires to 170 respondents who had prior experience shopping at both Alfamart and Alfagift. The data collected were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess the structural relationships among the proposed variables. The findings indicate that consumer trust in offline stores and perceived confidence in online stores have significant effects on both information-seeking intention and purchase intention. Moreover, information-seeking intention is found to significantly mediate the relationship between trust, perceived confidence, and consumers’ eventual purchase intention.